Komitmen Orang Tua Dalam Pendidikan Anak - Idam Mustofa (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
This study examines the values ​​of education of the Prophet Nuh AS contained in the QS. Hud verse 42-46 which can be a systematic guide to parents and continuously with the concepts of education of akhlak. After passing the content analysis can be formulated the firmness of Noah in the invitation of Kan'an to believe in showing his great commitment as a parent in the education of the akhlak. The call to goodness is an active and effective communication. This communication pattern can be used as a method of educating children in families. In this case the proposition that can be raised is the determination of parents' determination to save their children from infidelity by establishing simultaneous interactions.